THE RELATIONSHIP BETWEEN CAREER DEVELOPMENT CENTER INFORMATION SERVICES AND STUDENTS' CAREER PLANNING SKILLS AT UIN RADEN FATAH PALEMBANG - Rizki, Dyaz; Rasmanah, Manah; Fitri, Hartika Utami (Jurnal Konseling Pendidikan Islam, 2024)
The purpose of this study was to determine the relationship between career development center information services and students' career planning skills. This study uses a quantitative approach with a correlational research type. The population amounted to 141 students. From the sampling technique used using Slovin, there was a sample of 59 students. Data collection techniques using questionnaires and documentation, with a total of 25 question items from each instrument. After testing the validity with the results of rcount greater than rtable, the data is declared valid. The data analysis technique used uses the product-moment correlation test. The results of this study indicate that from the results of the product-moment correlation data test, there is a relationship between career development center information services and career planning skills in the moderate category. The determination of the relationship is taken based on the interpretation of the correlation coefficient which is in the interval between 0.40 - 0.599. Based on data hypothesis testing in the research that has been done, there is no relationship between career development center services and students' career planning skills, there is a value of 0.528 which means that the relationship has a moderate relationship. However, in terms of the strength of the relationship between Career Development Center information services and student career planning, the strength of the relationship is quite strong. This means that this career planning ability is not too strongly related to the career development center information service or in other words, the career planning ability has a relationship but little.